REKAYASA PRODUKSI INDIKATOR OKSIGEN SEBAGAI PENDETEKSI KEBOCORAN KEMASAN - Fitri Muslimah, Endang Warsiki dan Ika Amalia Kartika (Jurnal Teknologi Industri Pertanian, 2018)
Handling improper packaging can lead to decrease the quality of product. This can be caused by a leakage in the packaging so that the gas and water enter the packaging.Efforts are made to inform early of the leaking by attaching the package with indicator which called leakage indicator. The aims of this research were to formulate, characterize and examine the performance of leakage indicator. The factors investigated were the effect of the amount of Ca added (1-8 g) in the formula, the mole ratio of glucose to methylene blue (0.8:1-4.8:1) and the concentration of methylene blue (1-2%)on duration of glucose to reduct methylene blue, sensitivity time, water content, irreversible property and performance of leakage indicator.The results showed thatthe best formula of indicator were7 and 8 g of Ca , 0.8:1-2.8:1 of mole ratio of glucose to methylene blue and 2% of concentration of methylene blue. The analysis ofvariance showedthat the amount of Ca and the mole ratio of glucose to methylene blue affected the time of reduction and water content while the sensitivity time was only influenced by the mole ratio of glucose to methylene blue.The best leakage indicator was obtained from the amount of Ca of 8 g and the mole ratio of glucose to methylene blue of 1.8:1. The leakage indicator had irreversible property with reduction time of 72 min, sensitivity time of 31 s and water content of 10.85%. The response of oxygen indicator showedthat the colour changedfrom white to purple.Keywords: leakage detector,methylene blue, oxygen indicator